Validity of systemic inflammatory response syndrome (SIRS) criteria, interleukin-6 and (MELD) score as prognostic tools in cirrhotic patients with acute renal failure admitted to Emergency Department in Suez Canal University Hospital, Egypt - Adel Hamed Elbaih; Miada Youssef Ahmed; Nader A.Nemr; Hossam Eldin EL-Bahaay; Magdy Ali Omera (Medicine Science, 2017)
Systemic inflammatory response syndrome (SIRS) is the body's response to an infectious or noninfectious insult. Cirrhotic patients are predisposed to infection due to an impaired immune function acute kidney injury (AKI), is a frequent problem, in cirrhotic patients. Renal failure following sepsis has been observed in 1 third of patients with cirrhosis and ascites the prognosis for patients with cirrhosis and renal failure is poor: Acute kidney injury (AKI), is a relatively frequent problem, occurring in approximately 20% of hospitalized patients with cirrhosis. The prognosis for patients with cirrhosis and renal failure is poor, this extremely poor outcome is probably related to the combination of liver and renal failure, as well as to associated complications.To evaluate the outcome of the acute kidney injury in cirrhotic patients by using SIRS, IL-6 and value of MELD score in order to early diagnosis and treatment to improve outcome and to decrease short term mortality.as prognostic tools. Cross sectional observational study with prospective data collection. Data collected from 72 cirrhotic patients with acute kidney injury. All patients were followed up for 3 months and outcome was recorded. The 3 months mortality was 58.33%. 59.7% of the patients express SIRS criteria on admission to Emergency Department. SIRS criteria were significantly correlated with both ER mortality and 3 month mortality, serum level of IL-6 was 157.53 ± 191.59 pg/ml, there was significant relation between ER mortality, overall mortality and presence of infection and IL-6 levels. The mean MELD score was 30.32 ± 5.01, and Expected 3 month mortality according to MELD score ranged between "6% - 71.3%". There was significant relation between ER and overall mortality and MELD score. Value of IL-6>36.5 pg/ml has sensitivity of 83.3%, specificity of 80%, SIRS score>2 has sensitivity of 47.62%, specificity of 93.33%, in prediction of overall mortality among cirrhotic patients with acute renal failure, Value of MELD score>28 has sensitivity of 80.95%, specificity of 80%, in prediction of overall mortality among cirrhotic patients with acute renal failure. [Med-Science 2017; 6(2.000): 319-27]